2022
DOI: 10.3389/fpsyg.2022.949288
|View full text |Cite
|
Sign up to set email alerts
|

Cruise traveling behavior post-COVID-19: An integrated model of health protection motivation, travel constraint and social learning

Abstract: Travel restrictions have harmed the cruise industry as a result of the COVID-19 pandemic. The goal of this study, which is attributed to permanent changes in the regulatory and social landscape, is to identify and examine the factors influencing post-COVID-19 cruise travel intention. To explain cruise travel intention, we developed a theoretical model incorporating health protection motivation, social learning and travel constraint theories. An online survey was conducted with 400 valid responses collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Yang et al [58] identified self-actualization, self-improvement, and behavioral control as key drivers of solo travel intention. Green solo trips can be more helpful during diseases and crises that threaten tourism [59]. In addition to maintaining the health of tourists, green solo trips protect the Hyrcanian Forests in line with the goals of the World Tourism Organization (UNWTO) and sustainable development programs.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [58] identified self-actualization, self-improvement, and behavioral control as key drivers of solo travel intention. Green solo trips can be more helpful during diseases and crises that threaten tourism [59]. In addition to maintaining the health of tourists, green solo trips protect the Hyrcanian Forests in line with the goals of the World Tourism Organization (UNWTO) and sustainable development programs.…”
Section: Discussionmentioning
confidence: 99%